Developing a knowledge management framework for an innovation team - El Enany, Nellie (Cranfield University, 2008)
In today’s current business world it is becoming exceedingly difficult not only for organisations to compete but also to sustain competitive advantage. Organisations are realising that the key to this is not only knowing what knowledge resides in the organisation but knowing how to use this knowledge to create an innovative and differentiated product or service. Organisational knowledge provides a platform for innovation and allows individuals across the organisation to share creative ideas and inject these ideas into reinventing existing products and services as well as designing and creating new ones. Innovation is enormously dependent on knowledge and therefore its availability and quality. As part of promoting innovation, organisations are assigning teams of employees to take part in creative and technical thinking meetings to support and promote innovative practices. They key to the success of these meetings, and ultimately the innovative practices they promote, is to ensure that their planning, follow-ups and the actual meeting itself are effectively managed, measured and monitored effectively. This thesis explores an innovation team and the ways in which their activities can be improved or changed through effective knowledge management hence ensuring the continued success and longevity of the organisation. The analysis of the findings highlighted the importance of promoting innovative activities, knowledge management tools and planning and monitoring all stages of a meeting and its outputs. The research carried out enabled a knowledge management framework for an innovation team to be developed highlighting areas were key changes or improvements were required. It is anticipated that the framework will assist innovation teams to appreciate that all the stages of an innovation activity are vital specifically the outputs in both an explicit and tacit form.